Assessment of Verbal and Visuospatial Performance Predicting Cognitive Impairment in a Monolingual, Spanish-Speaking Sample. (30th August 2019) - Castillo, L; Campos, K; Soble, J R
Abstract: Objective: The Batería Neuropsicológica en Español (BNE) – Digit Span (DS) and Spatial Span (SS) subtests are popular instruments used to measure the capacity of verbal and visuospatial attention/working memory. Although deficits in working memory performance have been found in cases of mild cognitive impairment and dementia in analogous versions of these tasks among English speakers, very few studies have assessed the ability of verbal and visuospatial span tasks to identify impairment within a mono-lingual Spanish-speaking population. This study investigated the clinical utility of the BNE verbal and visuospatial span tasks for discriminating those with and without cognitive impairment in a Spanish-speaking Hispanic population. Participants and Method: Participants were 46 monolingual, Spanish-speaking Hispanics, 28 women (60.9%) and 18 (39.1%) men (M age = 63.41 (SD = 14.54); M education = 8.41 (SD = 4.39), referred for neuropsychological evaluations, which included the BNE-DS/SS. Three patients with invalid performances were excluded. Of the remaining 46, 17 were cognitively intact following evaluation, whereas 29 met criteria for a neurocognitive disorder. Results: Logistic regression analysis revealed that although DS backward model was significant, both DS forward age/education-corrected T- scores (p = .878) and DS backward (p = .67), were not significant predictors of cognitive impairment. In contrast, both SS forward (p = .002) and backward (p = .022) were significant predictors of impairment status with respective classification accuracies of 63% and 76.1%. Conclusions: Findings suggest better performance on visuospatial working memory (SS) is associated with generally intact cognitive abilities and decreased odds of cognitive impairment in a sample of monolingual Spanish-Speaking Hispanics; whereas verbal working memory (DS) findings were less robust.